Association of Fatty Acid Synthase with Level of Fatty Acids in Osteoporosis Patients - Abeer Hassan Alwan; Ekhlass M. Taha (Ibn Al-Haitham Journal for Pure and Applied Sciences)
Osteoporosis (OP) is a bone disease that makes bones more brittle and increases the risk of fractures. Osteoporosis, the most common type in postmenopausal women, is characterized by decreased bone mineral density, skeletal microstructure disintegration, and increased bone fragility. Osteoporotic fractures are more common in women than breast cancer, myocardial infarction, or stroke, and they also incur higher hospital treatment costs. This study aims to assess the connection between fatty acid and BMI, T-score, lipid profile(Triglyceride (TG), Total Cholesterol (TC), High-density lipoprotein (HDL), low-density lipoprotein(LDL), Very low-density lipoprotein(VLDL)), Total Antioxidant Status (TAS), Total Oxidant Status (TOS), Fatty acid synthase (FAS). The current study included 120 participants. Serum samples from postmenopausal women were collected and divided into three groups: 40 patients with OP (G2), 40 patients with osteopenia (G1), and 40 women as the control group. Gas chromatography (GC) to determine the levels of fatty acids (FAs). (ELIZA) was used to determine the levels of FAS, Whereas (TAS), (TOS), and (Triglyceride (TG), Total Cholesterol (TC), High-density lipoprotein (HDL)) were assayed using a spectrophotometer. The study's findings showed that OP (G2) had a significantly lower serum FAS level than osteopenia (G1) and control. The levels of palmitic, stearic, oleic, lenolinic, and linoleic (TC, LDL) in the G2 group were significantly higher than those in the G1 group and the control group. The HDL, VLDL, TG, TAS, and TOS levels in G2 were considerably lower than those in G1 and the control group. According to the Receiver Operating Characteristic (ROC) analysis, FAS showed high sensitivity and specificity. In conclusion, the parameters of FAS, HDL, VLDL, TG, TAS, and TOS were effective in monitoring the progression of osteoporosis, as well as fatty acid level.